2018
DOI: 10.1177/2156759x18808128
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Comprehensive School Suicide Prevention Program

Abstract: Suicide is the third most common cause of death for youth aged 14-19. School counselors need a school-wide prevention plan to address the mental and emotional needs of students experiencing suicidal ideation and behaviors. Although researchers have suggested that suicide prevention programming and suicide screening programs lower the rate of adolescent deaths, a paucity of evidence-based, school-wide, comprehensive suicide prevention programs exists. Therefore, to fill a gap in research and training resources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The implementation science literature highlights the need for an organization “inner setting” with a culture and leadership that encourages utilization of evidence-based practices, as well as resources to facilitate implementation (Damschroder et al, 2009). Support from management and efforts to enable all stakeholders to have a voice in determining action plans are necessary for successful adoption (Granello & Zyromski, 2019). Given the broader lack of attention to the issue of suicide in the anti-trafficking movement, trainings for service providers will be inadequate unless accompanied by efforts to enhance buy-in among leadership and the facilitation of supportive work environments necessary for frontline staff to succeed.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation science literature highlights the need for an organization “inner setting” with a culture and leadership that encourages utilization of evidence-based practices, as well as resources to facilitate implementation (Damschroder et al, 2009). Support from management and efforts to enable all stakeholders to have a voice in determining action plans are necessary for successful adoption (Granello & Zyromski, 2019). Given the broader lack of attention to the issue of suicide in the anti-trafficking movement, trainings for service providers will be inadequate unless accompanied by efforts to enhance buy-in among leadership and the facilitation of supportive work environments necessary for frontline staff to succeed.…”
Section: Discussionmentioning
confidence: 99%
“…Imagine the mental health issues at schools when combining the pandemic and the new reliance on social media with impressionable adolescent students. School counselors are a factor in reducing suicide ideation in students through their training and school-wide prevention programs (Granello & Zyromski, 2018).…”
Section: Suicidementioning
confidence: 99%
“…Although suicide prevention is the responsibility of all, schools inherently are practical venues for suicide prevention efforts that target youth due to their access to large numbers of students. Even so, Granello and Zyromski's (2019) recent review of school-based suicide prevention programs yielded a dearth of evidence-based programs among the research literature. Moreover, the programs they did identify witnessed significant deficits in reliability and validity measures, documentation of program fidelity, and/or demonstrated significance, both educational and clinical.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…With this in mind, the methods of suicide prevention presented with this literature review are among those that have garnered the greatest support from the research literature. Included in the discussion are programs and practices pertinent to the four types that Granello and Zyromski (2019) identified in their aforementioned review (i.e., universal suicide education, suicide screening and assessment, gatekeeper education, and programs to enhance students' protective factors) and one other program type, group skills training, that Katz et al (2013) identified in their earlier review of suicide prevention programs.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation